Diversity acceptance in question: enriching and adverse experiences in training and early professional practice in psychology - Winkler Müller, María Inés; Reyes Espejo, María Isabel (Acta Bioethica, 2017)
Faced with an ambiguous regulatory framework of professional practice in the country; and a practice of psychology in the context of a fuzzy professional identity and without clear boundaries with other professions, the importance of knowing crosscutting issues that concern the relationship with the other is relieved. This study explored the perception a group of students and novel psychologists about the training received and their first work experience, specifically in issues of interculturality and ethics; as well as on strengths and weaknesses of the training received. Eighteen individual interviews and two focus groups with 12 participants, from two state universities was conducted (N = 30). A intersubjectively categorical analysis was applied and four main categories emerged: context, positive, and adverse experiences in training, notion of interculturality, and suggestions for training in ethics and interculturality. We conclude on some challenges facing the formation of psychologists in Chile.